Managing across diverse cultures in East Asia : issues and challenges in a changing globalized world - Warner, Malcolm (London : Routledge, 2013)
'Why'Managing across diverse cultures in East Asia'? We re-examine in this book the link between culture and management across the region vis a vis the new economic, political and social landscape that has appeared over the last decade. We accordingly present a set of chapters on East Asian cultures, economies, societies and their management across the board, focusing on countries such as China, Japan, South Korea, as well as the Overseas Chinese enclaves of Hong Kong SAR, Macao and Taiwan. The contributors to this edited book are all specialists in their respective fields; they hail from a variety of universities and business schools across the world, located in a wide range of countries in the East and in the West. The chapters, we believe, reflect a balance between the past and present, theory and practice, as well as the general and the particular.'East Asia could not be more important. Malcolm Warner could not be more insightful. Reading Managing Across Diverse Cultures in East Asia will allow you to gain a profound understanding of the cultural complexity in this dynamic region of the world.' - Nancy J. Adler, McGill University, Montreal'We all need to understand more about management in East Asia, and to learn from it. Managing Across Diverse Cultures in East Asia has contributions from international experts who provide significant insights into the cultures of the most dynamic region in the world today. This book is a landmark publication.' - John Child, University of Birmingham'This edited volume, with contributions by significant scholars from around the globe, provides a timely and penetrating review of management issues across East Asia, a region that rivals Europe and North American in economic significance and is still ascending. It is a must read for anyone who is interested in international management.' - Kwok Leung, City University of Hong Kong'Helping a new generation of readers interested in this important region to make better sense, Managing Across Diverse Cultures in East Asia is destined to become a new classic. I expect this well-researched book to be widely read, cited, and debated in the years to come.' - Mike W Peng, University of Texas at Dallas'Having had such unexpected disasters as earthquakes, floods and financial crises in recent years, we are increasingly dependent on people-management. Development of human resources, in turn, requires region-specific and organization-specific strategies. The present volume edited by Malcolm Warner points the reader to the secret of success in high-performing economies and firms in East Asia.' - Yoko Sano, Kaetsu University, Tokyo'--
'The recent global financial crisis has raised the possibility of re-ordering the international system both globally and regionally, and the inter-relationships between the players in East Asia have become more complex. This book focuses on the economic backgrounds, cultural settings and management systems of China, Hong Kong, Japan, South Korea and Taiwan'--
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Management -- East Asia; Management -- Cross-cultural studies; East Asia -- Economic conditions